Emergency thyroidectomy for poorly controlled hyperthyroidism in the context of war in Ukraine - S. I. Savoliuk; A. Ye. Kovalenko; A. V. Zabronskyi (Сучасні медичні технології, 2025)
The aim of the work is to analyze the results of surgical treatment of patients with hyperthyroidism (Graves’ disease, multinodular toxic goiter, solitary toxic adenomas) in patients who were observed during the period of hostilities in Ukraine.